Analiza razlik med metodami avtomatskega določanja razvodnic na primeru povodja Rokave - Petkovšek, Gregor (Acta hydrotechnica, 2001)
The paper presents two methods for automatic catchment delineation based on a digital elevation model with a spational resolution of 25 m. First, the D8 algorithm was used, extended with the recent false depression handling methods. Then, a tool based on the DEMON-Upslope algorithm was developed. The accuracy of the two methods was tested on the Rokava watershed. A comparison with the delineation, based on the contours of a 1:5000 topographic map, was carried out. Both methods, when used with the DEM25, turned out to be appropriate for catchment delineation up to the sixth level, especially in the steeper part of the catchment. The D8 algorithm made some mistakes on the long slopes, which run in a direction different from a cardinal direction. The Rokava catchment lies in the coastal part of Slovenia; therefore, the results are representative for the Mediterranean countries, with the exception of the karst areas.
Keywords: D8, DEMON-Upslope; gričevnat svet; hidrologija; hilly terrain; hydrology; Rokava; Slovenia; Slovenija